Effect of Exercise Training on 1, 25(OH)2D Levels: The FIT-AGEING Randomized Controlled Trial. (July 2022) - De-la-O, Alejandro; Jurado-Fasoli, Lucas; Castillo, Manuel J.; Gutiérrez, Ángel; Amaro-Gahete, Francisco J.
Background: Vitamin D deficiency is currently endemic worldwide and is considered as an important factor in the development of several chronic conditions. Physical exercise has been postulated as an auspicious strategy to counteract age-related disorders preventing premature mortality. However, the effects of chronic exercise training on 1, 25-dihydroxyvitamin D [1, 25(OH)2 D] is unclear. This 12-week randomized controlled trial aimed to investigate the effects of different training modalities on 1, 25(OH)2 D in healthy sedentary adults. Hypothesis: Exercise training will increase 1, 25(OH)2 D in the study cohort. Study Design: Randomized controlled clinical trial. Level of Evidence: Level 1. Methods: A total of 89 healthy sedentary adults (53% women; 53.5 ± 4.9 years old) were enrolled in the FIT-AGEING study. The participants were randomized to (1) a control group (no exercise), (2) physical activity recommendation from the World Health Organization (PAR group), (3) high-intensity interval training (HIIT group), and (4) HIIT adding whole-body electromyostimulation training (HIIT + EMS). 1, 25(OH)2 D plasma levels were measured using a DiaSorin Liaison immunochemiluminometric analyzer. Results: Compared with the control group, 1, 25(OH)2 D increased in PAR (Δ = 10.99 ± 3.44 pg/mL; P = 0.01), HIIT (Δ = 11.63 ± 3.51 pg/mL; P = 0.009), and HIIT + EMS groups (Δ = 14.01 ± 3.59 pg/mL; P = 0.001) without statistical differences between them (all P s > 0.1). Conclusion: In summary, the results show that a 12-week exercise intervention produced an increment of 1, 25(OH)2 D independently of age, sex, and exercise modality in healthy sedentary adults. Clinical Relevance: The implementation of physical exercise could be considered a strategy not only aiming to reverse the seasonal decrease of 1, 25(OH)2 D in winter explained by low sunlight exposure but also for obtaining subsequent increases of this hormone even in these a priori adverse conditions.